Fostering Independence While Teaching Students With or at Risk for Reading Disabilities. (November 2021) - Hall, Colby; Dahl-Leonard, Katlynn; Denton, Carolyn A.; Stevens, Elizabeth A.; Capin, Philip
The Gradual Release of Responsibility (GRR) model for instructional delivery is well supported by research evidence and is often identified as a critical element of instruction for students with learning difficulties. However, there are challenges associated with effectively releasing responsibility to students. This may be especially true during instruction for primary-grade students with or at risk for learning disabilities. In general, educators want to provide a high level of support to young, struggling students in order to ensure that they feel successful and bolster their confidence. However, too much support means that students are not provided with opportunities for independent practice or independent mastery of content being taught. This article describes the GRR model of instruction and provides specific guidance and resources to support special education teachers in implementing the GRR model during small-group reading instruction in primary-grade classrooms, with a particular emphasis on facilitating group and independent practice.